{ x = − 2 y + 7 ( x − 1 ) 2 + ( y + 2 ) 2 = 20 {\displaystyle {\begin{cases}x=-2y+7\\(x-1)^{2}+(y+2)^{2}=20\\\end{cases}}}
( x − 1 ) 2 + ( y + 2 ) 2 = 20 ( − 2 y + 6 ) 2 + ( y + 2 ) 2 = 20 4 y 2 − 24 y + 36 + y 2 + 4 y + 4 = 20 5 y 2 − 20 y + 20 = 0 y 2 − 4 y + 4 = 0 4 ± 16 − 4 ∗ 4 2 y = 2 x = − 2 ∗ 2 + 7 = 3 ( 3 , 2 ) {\displaystyle {\begin{aligned}(x-1)^{2}+(y+2)^{2}=20\\(-2y+6)^{2}+(y+2)^{2}=20\\4y^{2}-24y+36+y^{2}+4y+4=20\\5y^{2}-20y+20=0\\y^{2}-4y+4=0\\{\frac {4\pm {\sqrt {16-4*4}}}{2}}\\y=2\\x=-2*2+7=3(3,2)\end{aligned}}}